PKM Sosialisasi Pembelajaran Keterampilan Gerak Dasar untuk Sekolah Dasar di Kota Makassar - Zulfikar, Muhammad; Hasmyati, Hasmyati; Anwar, Nur Indah Atifah; Mappanyukki, Andi Atssam; Haeril, Haeril (Universitas PGRI Semarang, 2023)
Fundamental movement skills provide an important foundation for elementary school students in their future participation in a variety of physical activities. This community service activity in the form of soialization aims to provide comprehensive knowledge about the importance of learning of fundamental movement skills for students' future and practical implementation in physical education learning. The partner's problem in this activity is that there is still a lack of understanding and not optimal learning of fundamental movement skills in physical education learning at school. The partner in this activity is SD Hang Tuah Makassar, Makassar City, South Sulawesi Province. This socialization activity was divided into several series of activities, namely: (1) Discussion of material with the teacher regarding learning fundamental movement skills, (2) discussion with the teacher regarding learning basic locomotor, non-locomotor and manipulative movement skills based on the theory of fundamental movement skills, and (4) Practice examples of learning fundamental movement skills for students. This activity provided results, namely a comprehensive understanding for teachers and students of the importance of mastering and learning of fundamental movement skills.